Diseño de un producto elaborado a partir del aceite de semilla de Sacha inchi (2020)
The Amazonian seed of sacha inchi stands out for its beneficial properties for health. The balanced content of omega 3, 6 and 9 can be highlighted. From this, an oil can be extracted that at the moment of characterizing it gives a density of 0.958 g/cm3, an apparent viscosity of 37.5 cP and a measure of 76ðBrix total soluble solids. In addition, the percentage of free fatty acids of 0.135%; iodine value of 193.519 g iodine/100 g oil; saponification number of 165.465 mg KOH/g fat; Peroxide value of 5,865 m-eq O2/kg of fat. Given its properties, it is proposed for sale to the public. For this, a survey was carried out, in which 90% of the respondents did not know its benefits, however, 24.24% would like to see a product type dressing. In this way, two dressings were made: traditional and light. An experimental design was proposed with which different formulations are presented for each of these. These were characterized to know their values of apparent viscosity, pH, acidity, stability and total soluble solids. Then, two samples of each type that had the best organoleptic conditions and lowest viscosities were selected. In this way, a sensory analysis of the Traditional 1 and 2, and Light 1 and 2 dressings was carried out. As they did not present significant statistical differences, the final products can be selected from the perception of the respondents and the analysis of the penalties. In this way, the chosen products were Traditional 1 and Light 2. For the first, values of 33.6ðBrix, a pH of 2.97, 1.95% acidity and a viscosity equal to 38500 cP were obtained. In addition, it was assigned a price of 33,766 COP for 250 mL considering that it has a cost of 21,104 COP. On the other hand, for the second, values of 16.3ðBrix, a pH of 3.4, 2.46% acidity and a viscosity equivalent to 9100 cP were obtained. Likewise, its cost is COP 18,689 and its price is COP 29,902.--Taken from the Degree Document Format.